Problems of Regulation of Gratification in Law Number 20 Of 2001 Concerning Amendments to Law Number 31 Of 1999 Concerning Eradication of Gratification Criminal Act of Corruption - Tantri Riyadi; Firdiawanti Firdiawanti; Toha Wangse (Yayasan Adra Karima Hubbi, 2025)
Background. This research aims to address the problem of regulating gratification in Article 12c of Law Number 20 of 2001. This provision provides the opportunity for state administrators to report gratuities within 30 days. Purpose. However, in its implementation, various problems still arise, both normatively, both practically and legally. Method. From a normative perspective, Article 12c does not explicitly explain what is meant by